Ecologia das interações entre Udranomia spitzi (Lepidoptera, Hesperiidae) e formigas tendo como hospedeira Ouratea spectabilis (Ochnaceae) em um cerrado mineiro - Bächtold, Alexandra (2010)
Studies in multitrophic systems can serve as tools to investigate the structure and organization of ecological communities. Because it is a biome rich in multitrophic interactions, the Cerrado (tropical savanna) is a good model for the study of insect-plant interactions. Udranomia spitzi (Hesperiidae) is an endemic butterfly from Cerrado. In the immature stage, it shows a pattern of specialized diet on young leaves of Ouratea spectabilis (Ochnaceae). These plants have nectaries on the base of the stipules of the leaves in development, encouraging visitation by ants and promoting interactions between ants and Udranomia larvae. Considered generalist predators, ants may exert strong selective pressure on insect herbivores, affecting the pattern of host plant use and strategies of defense against predators. Therefore, this study aimed to characterize the natural history, life cycle and behavioral ecology of Udranomia spitzi through the defensive mechanisms against ants. The study of this system was conducted in a Cerrado area of Uberlândia, Minas Gerais state, Brazil, from April 2008 to May 2009. To describe the cycle, individuals Udranomia were reared in the laboratory and information about its natural history were derived from field and laboratory observations. Interactions between Udranomia spitzi caterpillar and ants were recorded during provoked encounters to investigate the defense strategies of the butterfly. Experiments involving exclusion of ants were used to elucidate if the presence of ants affects the survival of U. spitzi larva. The results showed that U. spitzi has five instars in their immature stage and presents morphological and behavioural similarities to other members of Hesperiidae. Its larvae are able to build up two types of leaf shelters for most of their ontogeny and only one larva is found in each shelter. The larvae feed and build shelters only on young leaves of O. spectabilis, in proximity to the location of extrafloral nectaries. Thus, the chances the larvae will be found by ants increases. In response, the immatures have different mechanisms of defense against predation, in addition to the shelters. It was observed that when larvae of U. spitzi were attacked, they violently move their body and regurgitate fluids on the ants. These defensive responses were effective only for larger larvae (from 4th instar), compared to smaller (2nd instar). Once located the larvae of 2nd instar had little time to escape from the predator. Experiments involving the exclusion of ants revealed that the presence of ants affects the survival of larval U.spitzi over the time. This study showed the importance of to the developed defense strategies of to the larvae of Lepidoptera, as U. spitzi, that permited them to use a plant often occupied by ants in the Cerrado.